Implementation of Problem-Based Learning Assisted by Canva to Complete Assignments in Science Learning for Class V SDN Kendal - Mulatiningsih Mulatiningsih; Sulastri Rini Rindrayani (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This conceptual study discusses the implementation of the Problem-Based Learning (PBL) model assisted by Canva to support task completion in the Science and Social Studies (IPAS) subject for fifth-grade students at SDN Kendal. The PBL model encourages students to actively solve contextual problems, while Canva serves as an interactive visual tool to enhance idea presentation and student outcomes. This study outlines the implementation stages based on PBL syntax: problem orientation, organization, investigation, development and presentation, as well as analysis and evaluation. The findings indicate that integrating PBL with Canva enhances students' critical thinking, creativity, visual literacy, and communication skills. Challenges such as limited device access and varying levels of digital literacy can be addressed through short training, time management, and alternative manual tasks. This study recommends this approach as an innovative strategy to improve the effectiveness of IPAS learning at the elementary level.